Pengaruh Profitabilitas dan Likuiditas Terhadap Kebijakan Dividen Pada PT. Sepatu Bata TBK - I Gusti Ayu Diah Dhyanasaridewi; Ni Made Artini (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2020)
Dividend policy is one of the functions of financial management apart from investment and funding decisions made by companies or banks in making decisions about the profits they receive to be distributed to shareholders according to the shares they own as dividends or reinvested as retained earnings which are carried out based on the General Meeting. Shareholders (GMS). Gitman, L.J. (2009: 611) states that "the company's dividend policy must be formulated with two basic objectives, namely providing adequate financing and maximizing the wealth of the company owners." Investors have an interest in information about Return On Equity (ROE) and Current Ratio (CR), in predicting the distribution of dividends that will be received. Therefore, it is necessary to examine the influence of Profitability and Liquidity on the Dividend Distribution Policy. This analysis aims to determine the effect of profitability and liquidity on the amount of dividends distributed to shareholders in PT. Bata shoes. The research method used is quantitative by using secondary data in the form of financial statements of PT. Bata Shoes Tbk from 2015-2019